Ankyrin-G and Its Binding Partners in Neurons: Orchestrating the Molecular Structure of the Axon Initial Segment - Xiaowei Zhu; Yanyan Yu; Zhuqian Jiang; Yoshinori Otani; Masashi Fujitani (Biomolecules, 2025)
The axon initial segment (AIS) is a specialized subcellular domain that plays an essential role in action potential initiation and the diffusion barrier. A key organizer of the AIS is Ankyrin-G, a scaffolding protein responsible for clustering voltage-gated ion channels, cell adhesion molecules (CAMs), and cytoskeletal components at this critical neuronal domain. Recent proteomic analyses have revealed a complex network of proteins in the AIS, emphasizing Ankyrin-G’s central role in its molecular architecture. This review discusses new findings in the study of AIS-associated proteins. It explains how Ankyrin-G and its binding partners (such as ion channels, CAMs, spectrins, actin, and microtubule-associated proteins including end-binding protein 3, tripartite motif-containing protein 46, and calmodulin-regulated spectrin-associated protein 2) organize their structure. Understanding the dynamic regulation and molecular interactions within the AIS offers insights into neuronal excitability and reveals potential therapeutic targets for axonal dysfunction–related diseases. Through these dynamic interactions, Ankyrin-G ensures the proper alignment and dense clustering of key channel complexes, thereby maintaining the AIS’s distinctive molecular and functional identity. By further unraveling the complexity of Ankyrin-G’s interactome, our understanding of AIS formation, maintenance, and plasticity will be considerably enhanced, contributing to the elucidation of the pathogenesis of neurological and neuropsychiatric disorders.